Fatal disseminated mucormycosis due to Cunninghamella bertholletiae infection after ABO-incompatible living donor liver transplantation: a case report - Atsuyoshi Mita; Shohei Hirano; Takeshi Uehara; Kai Uehara; Yasunari Ohno; Koji Kubota; Yuichi Masuda; Tsuyoshi Notake; Kazuki Yoshizawa; Akira Shimizu; Yuji Soejima (Surgical Case Reports)
Abstract Background Fungal infection may develop because of immunosuppression after organ transplantation, in which invasive types, such as Aspergillus and Mucorales, fungi cause morbidity. We present a case of disseminated mucormycosis due to Cunninghamella bertholletiae after ABO-incompatible living donor liver transplantation (LDLT). Case presentation A 47-year-old man with decompensated liver cirrhosis and hepatocellular carcinoma underwent an ABO-incompatible LDLT using a graft procured from his son, who had a different blood type. Rituximab and mycophenolate mofetil were administered 3 weeks before LDLT as immunosuppressive therapy. Although liver graft function improved, mass-like infiltrates appeared in the lungs following intubation for > 1 week due to impaired consciousness. The brain magnetic resonance imaging findings were normal. Decreased ejection fraction and ST elevation were detected on echocardiography and electrocardiography, respectively. There was no dominant stenosis on coronary arteriography. The recipient underwent segmentectomy of the right lung 20 days after LDLT. C. bertholletiae was identified from a specimen using polymerase chain reaction, thus establishing a diagnosis of mucormycosis. Multiple infarctions in the brain, heart, and kidney developed within 2 weeks. Treatment with amphotericin B was ineffective. The patient developed circulatory collapse, and a temporary pacemaker and percutaneous coronary intervention were required for cardiac infarction. The recipient died of cardiac failure 27 days after the LDLT. Autopsy revealed disseminated mucormycosis involving the brain, thyroid, heart, lung, liver, gastrointestinal tract, and both kidneys. In addition, fungal endocarditis may have been responsible for septic emboli in multiple organs, resulting in multiple organ invasion. Hypothrombocytopenia was present since the pre-transplant period, and the recipient was diagnosed posthumously with myelodysplastic syndrome due to hereditary abnormalities. Multiple factors such as organ transplantation, bone marrow dysfunction, immunosuppression, and inadequate administration of antifungal reagents might have promoted mucormycosis development in our patient. Conclusions Mucormycosis by C. bertholletiae is a fatal complication; thus, early diagnosis and treatment are warranted before multiple organ invasion.